Empowerment, climate change adaptation, and agricultural production: Evidence from Niger - Wouterse, Fleur (Springer, 2017)
We use new household level data from Niger and regression analysis to study the role of drought perception and human capital—including empowerment—in climate change adaptation through the digging of zaї pits and effects of these pits on agricultural productivity. We find that selection of households into adoption of zaï pits is influenced by the perception that the frequency of droughts has increased. More educated, experienced, and empowered households are also more likely to have put in place zaï pits. Accounting for endogeneity of adoption, zaї pits are found to significantly increase cereal yields. Our counterfactual analysis reveals that even though all households would benefit from adoption of zai pits, the effect would be significantly larger for households that did not adopt if they had adopted. For the latter group, empowerment in particular is associated with significantly higher yields.